Learning Design on Cube and Cuboid Topics Based on Local Instruction Theory (LIT) - Utami, Tri Putri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The purpose of this study is to develop an instructional design for teaching cubes and cuboids based on Local Instruction Theory (LIT). This study employed a design research approach, which involved three phases: preparing for the experiment, designing the experiment, and conducting a retrospective analysis. The participants consisted of 32 students from Class VIII-3 at SMP Negeri 1 Banda Aceh and one teacher. In the preliminary stage, the Hypothetical Learning Trajectory (HLT) was designed based on the learning objectives, activities, and relevant media. The instructional experiment was carried out to implement the HLT, whereas the retrospective analysis was intended to evaluate the effectiveness of the applied learning trajectory. The findings indicate that a well-designed Hypothetical Learning Trajectory (HLT) can significantly improve students' understanding of cubes and cuboids.